Insektengiftallergie = Insect venom allergies : update 2016 for otorhinolaryngologists - Klimek, Ludger; Dippold, Nina; Sperl, Annette (HNO, 2016)
Due to the increasing incidence of hymenoptera venom allergies and the potentially life-threatening reactions, it is important for otolaryngologists working in allergology to have an understanding of modern diagnostic and treatment standards for this allergic disease. Molecular diagnosis with recombinant single allergens from bee and wasp venom components improves the diagnostics of insect venom allergies, particularly in patients with double-positive extract-based test results. Detection of specific sensitizations to bee or wasp venom enables double sensitizations to be better distinguished from cross-reactivity. Based on patient history and test results, the patient is initially advised on avoidance strategies and prescribed an emergency medication kit. Then, the indication for allergen-specific immunotherapy (AIT) is evaluated. The dose-increase phase can be performed using conventional, cluster, rush, or ultra-rush schedules, whereby rapid desensitization (rush AIT) performed in the clinic seems to be particularly effective as initial treatment.